2021
DOI: 10.1002/smll.202103705
|View full text |Cite
|
Sign up to set email alerts
|

Effective Screening Route for Highly Active and Selective Metal−Nitrogen‐Doped Carbon Catalysts in CO2 Electrochemical Reduction

Abstract: to CO suffer from sluggish reaction kinetics and ambiguous mechanism. [5] Therefore, efficient and selective electrocatalysts for the reduction of CO 2 to CO should be found.Metal-nitrogen−doped carbon (M-N-C) catalysts are promising candidates as catalysts for electrochemical conversion of CO 2 to CO. [6] M-N-C catalysts that include M-N 4 centers are similar to molecular metalloenzyme systems, which have tremendous potential for CO production. [7] Recently, numerous studies have constructed noble metal (Au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 64 publications
0
15
0
Order By: Relevance
“…All twelve active sites show that Δ G *H–*CO > 0, indicating that all of them are prone to CO 2 RR selectivity. 49 Although the lower HER energy barrier is considered to be conducive to the protonation process, it is undeniable that it brings greater HER selectivity. Herein, the intrinsic CO 2 RR activity of the sites was focused to reveal the activity regulatory mechanism controlled by dual M 1 /M 2 centers.…”
Section: Resultsmentioning
confidence: 99%
“…All twelve active sites show that Δ G *H–*CO > 0, indicating that all of them are prone to CO 2 RR selectivity. 49 Although the lower HER energy barrier is considered to be conducive to the protonation process, it is undeniable that it brings greater HER selectivity. Herein, the intrinsic CO 2 RR activity of the sites was focused to reveal the activity regulatory mechanism controlled by dual M 1 /M 2 centers.…”
Section: Resultsmentioning
confidence: 99%
“…From the results, there were 700 possible combinations (= 28 transition metals × 5 host heteroatoms × 5 dopant heteroatoms). The variation of the d- orbital for transition metals ultimately increases the catalytic performance by controlling the binding strength of electrocatalytic reaction intermediates in the hydrogen evolution reaction (HER), ORR, the oxygen evolution reaction (OER), and the carbon dioxide reduction reaction (CO 2 RR) ( Xu et al, 2018 ; Zhu et al, 2019 ; Park et al, 2021 ). Therefore, we considered 28 d -block transition metal elements, including 3 d (from Sc to Zn), 4 d (from Y to Cd), and 5 d (from Hf to Au).…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, DFT-based screening analyses have demonstrated that the MÀ NÀ C (M=Fe, Co, or Ni) materials are among the most structurally stable and experimentally operable (see Figure 13a). [106] In a recent study, it has been achieved good stability over 50 h for CO 2 -to-CO conversion on an SACbased NiÀ NÀ C catalyst featuring a pyrrole-type NiÀ N 4 structure. Additionally, a slight attenuation in both j and FE CO was observed, which resulted in ca.…”
Section: Mà Nà C (M = Fe Co or Ni) Catalysts For The Co 2 Rrmentioning
confidence: 99%